THE INFLUENCE OF KNOWLEDGE SHARING AND WORK ENGAGEMENT ON THE PERFORMANCE OF BENGKULU PROVINCE HEALTH OFFICE EMPLOYEES MEDIATED BY LOYALTY - Wilda Sri Fadilla Putri; Praningrum Praningrum (SEAN Institute, 2023)
This research aims to test and analyze the effect of knowledge sharing on employee performance at the Bengkulu Provincial Health Service, test and analyze the effect of work engagement on employee performance at the Bengkulu Provincial Health Service, test and analyze the effect of knowledge sharing on loyalty at the Bengkulu Provincial Health Service, test and analyzing the influence of work engagement on loyalty at the Bengkulu Provincial Health Service, testing and analyzing the influence of loyalty on employee performance at the Bengkulu Provincial Health Service. This research applies descriptive quantitative methods. Based on the results of the research and discussions carried out by the researchers, the following research conclusions were obtained: (1) Knowledge Sharing has a positive effect on employee performance, (2) Work Engagement has a positive effect on employee performance, (3) Knowledge Sharing has a positive effect on loyalty, (4) Work Engagement has a positive effect on loyalty, (5) Loyalty has a positive effect on employee performance.